CONTINUOUS EXPERTS COACHING TO INCREASE THE COMPETENCE OF PARTICIPANTS OF THE INCLUSIVE PROCESS IN EDUCATIONAL INSTITUTIONS - Skrypnyk, Tetiana; Biryukova, Karina (Continuing Professional Education: Theory and Practice, 2020)
In the article, the authors analyze ways to increase the professional competence of teachers of multidisciplinary IEP teams. This allows the conclusion that that the use of coaching is appropriate for mastering support specialists with inclusive technologies, as well as the ability to work in a team interaction mode. Despite the obvious advantages of teamwork, in Ukraine this format of work is still not mastered in an inclusive educational environment. In the article the authors present the structure of the training program based on the team management model for significant achievements (R. Hackman). We conducted a training program for 10 IEP teams, aimed at increasing the level of team interaction and inclusive competence of specialists. Formative influence was done directly during the professional activity of teachers and was accompanied by prolonged expert coaching. In their study, the authors applied a special design scheme for teamwork. This scheme was concretized in the fact that the participants of the IEP teams used the experience gained in the training sessions in the practice of their professional activity, critically comprehended and analyzed their new experience, sought to comprehend the factors of both success and failure. Together with the coordinator and experts, all participants of the IEP teams developed rules for the team, established feedback, sought to influence the focus on mastering the modern approaches of the inclusive process at the level of the entire educational institution. In turn, this maintained the necessary level of motivation and joint intentions to introduce a competently constructed educational environment. To assess the state of inclusive competence formation before and after the training program, we used teacher self-assessment method «Professional Development Tool for Improving the Quality of Practice in primary school». As a result, all teachers have achieved a significant increase in the effectiveness of interdisciplinary support for children with special needs, which have reflected in the positive changes that have occurred in teachers at the professional, interpersonal and personal levels.